Benchmarking Methods in Georgian Energy Sector - Sulakadze, Lana (European Scientific Journal, ESJ, 2017)
The purpose of the study is to compare the approaches taken by a variety of energy regulators to implement benchmarking for distribution network companies. The findings shall serve as baseline for development of the incentive based methodology. Research methods: Based on the practical significance of the research problem we used systemic, historical and logical generalization methods of research in the performance of the work. Scientific abstraction, analysis and synthesis methods are also used. Results: To evaluate the effectiveness of Georgian companies we can’t use the comparative analysis’s methods that are used by the EU Regulators, because the market is monopolized and the companies don’t have a similar structure and financial conditions. Conclusions: As a result, in Georgia it’s much better to use the Activity Based Costing (ABC) method for a short-term analysis and international comparative analysis for the long-term period.